Nicotine – Metal ion interactions in solutions: Potentiometric, cyclic voltammetry investigations and quantum chemical calculations. (September 2017) - Fazary, Ahmed E.; Ju, Yi-Hsu; Fawy, Khaled F.; Al-Shihri, Ayed S.; Bani-Fwaz, Mutasem Z.; Alfaifi, Mohammad Y.; Shati, Ali A.; Elbehairi, Serag Eldin I.; Abd-Rabboh, Hisham S.M.
Highlights: Iron(III) metal ion formed the most stable nicotine complexes. Most of the nicotine complexes was started to form at pH equal to 3.8, reached maximum formation from 40 to 80 % at pH ranging from 4.5 to 7.5, and all these complex species disappeared in the solutions at pH > 8. The formation process of the nicotine complexes was found to be spontaneous and exothermic. The nicotine complexes appear to be superior in biological properties to ligand alone. Abstract: The experimental protonation and complex formation equilibrium constants of nicotine (NIC) with trivalent (iron (III), and chromium (III)) and divalent (copper (II), and nickel (II)) metal ions have been investigated at 310.15 o K in water solutions at ionic strength of 13.60 g·dm −3 NaNO3 using pH-potentiometric and cyclic voltammetry techniques, and by means of Hyperquad 2008 estimation model program. Also, the dissociation constants of NIC and the equilibrium constants of its binary complexes with the studied metal ions in 13.60 g·dm −3 NaNO3 water solutions were observed at different temperatures such as (298.15, 310.15, 318.15 and 328.15) K. The theoretical calculations of overall protonation and stability constants of the metal ion-nicotine complex species in aqueous solutions were predicted as the Gibbs energy change associated with the nicotine protonation, and metal ion – nicotine complex formation equilibria using ab initio and density function theory calculations by applying Gaussian 09 software molecular modeling. The usage of the experimental potentiometry/spectrophotometry techniques and theoretical predictions provides a complete picture of the microscopic equilibria of the studied systems (metal ions -nicotinate). Precisely, this theoretically predications could be useful to control the most real protonation constants of nicotine ligand in which the binding sites changes due to the ligand protonation/deprotonation equilibria. Also, the complexing capacities of different metal ions towards nicotine in solutions were evaluated and discussed. From the determined experimental stability constants of different metal complex species, the concentration distribution diagrams of the various metal ions - nicotine complex species in solutions were estimated using HySS 2009 software.